Análisis del Rendimiento de los Frameworks de Desarrollo IONICS vs Apache Cordova Aplicado al Sistema de Notificación de Eventos de la Unach, 2018 - Duchi Quishpe, Jorge Luis (2019)
Over the years, technology has grown significantly, thus the small, medium and large companies, organizations, public and private institutions have been improved. They have tried to adapt to the change of this new era. New technological tools have turned up such as development frameworks for hybrid mobile applications. Therefore, this investigation aimed to the analysis of the performance between the Ionic vs. Apache Cordova development frameworks applied to the system notification of activities at National University of Chimborazo (UNACH). This research is experimental since no test groups are established for research, hence, according to the level of knowledge, the research was descriptive since data of the measurement parameters were obtained for later statistical analysis. The deductive and analytical method were also considered because the study was separated, that is the Study was analyzed it individually, since it is a comparison of independent samples in a set period of time. Measurements were made for two weeks on the Sony Xperia mobile device XA1, which has installed the two applications developed with the frameworks. The application manager was applied since it is already installed in the system versions Android mobile operating system, which measures the performance of the device and the applications installed, 400 measurement data were obtained in the established time, for this case, a random sample was determined within an infinite population, once the data was obtained, the Mann-Whitney U statistical test it was determined that data are not normalized, in the end the null hypothesis was rejected, and the research´s hypothesis accepted, which mentions that there is a difference performance between Ionic and Apache Cordova.